The Effect of Beauty Privilege on the Recruitment Process of Hotel Employees in Bali - Cahyo Purnomo Loanata; I Gusti Agung Gede Witarsana; Made Uttari Pitanatri (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of this research is to see how beauty privilege affects the hiring process in Bali's hospitality industry as the industry plays an important role in the regional economy and the selection of high-quality human resources is crucial to the quality of service provided. The research method is qualitative, using phenomenological study, descriptive analysis and interviews. The research involved interviews and literature study with hospitality professionals, including managers and human resource management staff. The results showed that while beauty privilege may be considered when selecting candidates for employment, especially for guest-facing jobs, factors such as attitude, ability and knowledge (ASK) remain the most important. Practitioners agree that if a candidate has the necessary abilities, physical appearance is not important. Also, while appearance may be beneficial, the main focus remains on abilities that support performance and fit the company culture. The emphasis on professional demeanor and technical ability demonstrates this. To reduce biases related to physical appearance in the hospitality industry, this research suggests that recruitment standards should be more fair and inclusive.